Association of Infertility with Quality of Life among Infertile Married Couples - Sadia Chaudhary, Fatima Aslam, Unaiza Jawad, Muhammad Waqas Rabbani, Syed Ahmed Mahmud, Hina Jawaid, Saqib Rabbani, Waqas Latif (Pakistan Journal of Medical & Health Sciences, 2022)
Infertility is believed very difficult and sensitive issue for wedded couples, particularly those who have passed several years of married life. Infertile married couples could experience mental distress and also suffer from impaired health-related QoL. Aims: To assess the association of infertility with quality of life among married couples. Study Design: Cross-sectional study. Methodology: Present study enrolled 140 couples who were actively trying for conception for 3 years visiting Hameed Latif Hospital Lahore were included. Non-probability purposive sampling technique was used. Informed written consent was taken from all the participants. The overall mean score of quality of life measured by WHOQOL-BREF questionnaire. Statistical analysis: To check the correlation of infertility with quality of life, Spearman’s/ Pearson correlation was used. The P value of < 0.05 was considered as significant. Results: Out of 140 couples, mean age was 31.6±3.0 years. The mean age of female participants was 30.1 ± 2.8 and the mean age of male participants was 33.1 ± 2.4. The overall mean score of quality of life measured by WHOQOL-BREF questionnaire was 98.2 ± 11.5. The mean score of quality of life of male participants was 98.5 ± 11.5 and mean score of quality of life of female participants was 98.0 ± 11.6. Conclusion: It was concluded that quality of life of majority of the couples was not affected due to infertility.